A Legal Analysis of Freeze-Dried Human Milk Classification as Functional Food, Human-Derived Substance, or Medical Product in Indonesia - Arifin Kurniawan Kashmir; Happy Yulia Anggraeni (Research Horizon, 2026)
Freeze-dried human milk from donor milk poses a regulatory challenge in health law due to its human origin, clinical use, and unclear legal classification. This study aims to determine the appropriate legal classification of freeze-dried human milk under the Indonesian health law framework and to formulate a proportionate regulatory approach for its governance. The study uses a normative legal method with statutory, conceptual, comparative, and health policy approaches, based on Indonesia’s Health Law Number 17 of 2023, Government Regulation Number 28 of 2024, and Regulation (EU) 2024/1938 on Substances of Human Origin, supported by literature on donor human milk, milk banking, processing, and commercialization of human-derived materials. The study finds that a purely food-based classification is legally underinclusive because it fails to address donor screening, traceability, and biovigilance obligations, whereas classification as a substance of human origin is normatively more coherent but remains insufficient unless coupled with enteral safety controls. By contrast, classification as a medical product may be justified only in limited clinical contexts and risks excessive medicalization. Freeze-dried human milk should be regulated under a hybrid framework combining human-origin substance governance, food safety, and clinical oversight to ensure infant safety, donor protection, equitable access, and prevent commodification.